Insulation sealing grease composition and preparation method thereof

By using an insulating sealing grease composition with a specific ratio in the sealing grease, the problems of low viscosity, poor adhesion and poor adhesion of the ordinary sealing grease base oil are solved, and high viscosity, excellent sealing performance and good chemical stability of the sealing grease are achieved.

CN119842429AActive Publication Date: 2025-04-18HUBEI BODA SPECIAL LUBRICANT CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510331842.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-04-18
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

The base oil of commercially available ordinary sealing grease has low viscosity, poor adhesion and poor adhesion, which affects the stability and sealing effect of the sealing grease.

Method used

An insulating sealing grease composition is adopted, including base oil, anti-rust agent, thickening agent, modified bentonite, calcium carbonate, modified asbestos fiber, surface modifier and antioxidant. Through the combination of these components, the viscosity, sealing performance and chemical stability of the sealing grease are improved.

Benefits of technology

It significantly improves the viscosity, sealing performance and chemical stability of the sealing grease, extends the service life of the parts, and enhances the stability and reliability of the sealing grease in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of lubricating grease, and particularly discloses an insulating sealing grease composition and a preparation method thereof. The insulating sealing grease composition is prepared from the following raw materials in parts by weight: 60 to 90 parts of base oil, 2.5 to 3.5 parts of antirust agent, 7 to 12 parts of thickening agent, 11 to 15 parts of modified bentonite, 4 to 6 parts of calcium carbonate, 8 to 12 parts of modified asbestos fiber, 1.6 to 1.8 parts of surface modifier and 2.4 to 2.7 parts of antioxidant. The insulation sealing grease composition prepared in the invention has excellent electrical insulation performance, sealing performance and temperature resistance, can provide mechanical protection and sealing performance for parts, reduces damage caused by vibration, impact and wear, and prolongs the service life of the parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lubricating grease, and in particular to an insulating sealing grease composition and a preparation method thereof. Background Art

[0002] Sealing grease composition is a paste composed of liquid and solid materials, which is mainly used to meet the sealing function of the connection or sealing of the objects (such as workpieces) under a certain pressure. Its main components include liquid components and solid components. The liquid components are mostly organic liquids, such as mineral oil, silicone oil, etc. These liquid components provide the fluidity and lubricity of the sealing grease. The solid components include tiny particles of various sizes, both organic and inorganic. For example, graphite, white carbon black, talcum powder, polytetrafluoroethylene powder, asbestos wool, etc. These solid components enhance the sealing performance and high temperature resistance of the sealing grease.

[0003] In the prior art, the preparation method of the sealing grease composition generally includes mixing a base oil, a thickener, an organic filler and an inorganic filler, and then grinding the mixture to obtain a sealing grease product with excellent performance, which is widely used in multiple fields such as industry, construction, and automobiles, and has excellent sealing performance, lubricity, high temperature resistance, and chemical resistance. However, the base oil of common sealing greases available on the market is also mineral oil or ester-based synthetic oil, which generally has low viscosity, poor adhesion, and weak adhesion, thereby affecting the stability and sealing effect of the sealing grease. Summary of the invention

[0004] In order to improve the problems of low viscosity, poor adhesion and weak adhesion of common sealing grease, the present application provides an insulating sealing grease composition and a preparation method thereof.

[0005] The present application provides an insulating sealing grease composition, which adopts the following technical solution: An insulating sealing grease composition comprises the following raw materials, measured by weight: 60-90 parts of base oil, 2.5-3.5 parts of rust inhibitor, 7-12 parts of thickener, 11-15 parts of modified bentonite, 4-6 parts of calcium carbonate, 8-12 parts of modified asbestos fiber, 1.6-1.8 parts of surface modifier and 2.4-2.7 parts of antioxidant.

[0006] By adopting the above technical solution, the base oil has good lubrication performance, fluidity and spreadability, can reduce the friction and wear of the components, extend the service life of the components, and improve the sealing effect. The base oil has excellent chemical stability and temperature resistance, can resist the erosion of various chemical substances, protect the components from corrosion, and the high dielectric strength and low dielectric constant of the base oil make it an ideal insulating medium, which helps to improve the electrical insulation performance of the sealing grease. The rust inhibitor can form a protective film to prevent the metal surface from contacting with corrosive substances such as oxygen and moisture in the air, further enhance the rust prevention effect of the sealing grease, and improve the chemical stability of the sealing grease composition, so that it can still maintain good performance in harsh environments.

[0007] Thickeners can convert liquid base oil into a semi-solid to solid structure. Through the thickening effect of thickeners, sealing grease can maintain its position in the complex structure of the component, provide continuous sealing and insulation effects, and maintain its shape and performance, prevent oil separation, and ensure the uniformity and consistency of the sealing grease during use. Modified bentonite has good colloidal properties, can effectively thicken the base oil, form a stable colloidal structure, and make the sealing grease difficult to flow. Modified bentonite can expand when exposed to water, fill irregular cavities, enhance the sealing performance of the sealing grease, and improve the temperature resistance and chemical stability of the composition.

[0008] Calcium carbonate increases the volume of sealing grease, and through its fine particle structure, it enhances the mechanical strength and hardness of the sealing grease, improves its wear resistance and pressure resistance, and can also improve the thixotropy of the sealing grease, maintaining a high viscosity when stationary, and reducing the viscosity when subjected to shear force, making it easier to apply and fill, while maintaining good shape stability after application. Modified asbestos fiber has a high tensile strength, which can significantly enhance the mechanical strength of the sealing grease, improve its wear resistance and pressure resistance, and make it less likely to be damaged when subjected to mechanical stress; it also has good high temperature resistance, sealing and chemical stability, which can enhance the stability and reliability of the sealing grease in high temperature environments, ensuring that it maintains its physical and chemical properties over a wide temperature range.

[0009] Surface modifiers can improve the dispersibility of various solid fillers (such as modified bentonite, calcium carbonate, and modified asbestos fibers) in sealing grease, ensuring that these components are evenly distributed in the base oil to avoid agglomeration and precipitation, thereby improving the overall performance and stability of the sealing grease. Antioxidants can capture and neutralize free radicals generated under high temperature and high pressure environments, preventing oxidation reactions of base oil and fillers, thereby improving the antioxidant stability of the sealing grease, extending the service life of the sealing grease, and reducing performance degradation and failure caused by oxidation. The insulating sealing grease composition obtained by mixing various components has excellent electrical insulation performance, sealing, and temperature resistance, can provide mechanical protection and sealing for components, reduce damage caused by vibration, impact, and wear, and extend the service life of components.

[0010] Preferably, the preparation method of the modified bentonite comprises the following steps: (1) dispersing bentonite and dimethyl octadecyl quaternary ammonium salt in deionized water, stirring at a temperature of 60-65° C. for 30-35 minutes, filtering, and drying to obtain pretreated bentonite; (2) dispersing graphene in deionized water, adding Triton X-100 and modified viscose fiber, stirring at a speed of 5000-5500 rpm for 20-25 min, and drying to obtain pretreated graphene; (3) Dispersing the pretreated bentonite in step (1) in an acetic acid solution, adding the pretreated graphene and chitosan in step (2), stirring at a temperature of 70-75° C. for 2-3 h, and drying to obtain modified bentonite.

[0011] By adopting the above technical solution, dimethyl octadecyl quaternary ammonium salt can be adsorbed on the surface of bentonite particles, and the agglomeration of bentonite particles can be prevented through electrostatic repulsion and steric hindrance effects, thereby improving its dispersibility in water and forming a stable suspension, which is helpful for the subsequent mixing of bentonite with other components.

[0012] Triton X-100 can be adsorbed on the surface of graphene sheets, and through electrostatic repulsion and steric hindrance effects, it can prevent graphene sheets from agglomerating, improve the dispersibility of graphene in water, and form a stable graphene aqueous solution. Modified viscose fiber can be loaded on the surface of graphene. Graphene has extremely high strength and good thermochemical stability, which can enhance the mechanical strength and electrical insulation properties of sealing grease and improve its sealing effect in complex environments. Viscose fiber can increase the flexibility and ductility of sealing grease, so that it maintains good sealing performance under different temperature and pressure conditions. Triton X-100 can improve the compatibility between graphene and viscose fiber, promote the uniform dispersion of the two in aqueous solution, form a stable graphene / viscose fiber composite system, enhance the mechanical properties and functionality of the composite material, and the obtained pretreated graphene has good mechanical properties, thermal stability and corrosion resistance, extending its service life.

[0013] Pretreated bentonite, pretreated graphene and chitosan are mixed. Graphene can be loaded on the surface and pores of bentonite to improve the mechanical properties, thermal stability and chemical stability of bentonite. Chitosan has a certain viscosity, which makes bentonite and graphene adhere tightly. Graphene can be stably loaded on the surface of bentonite. The obtained modified bentonite has good mechanical properties, thermal stability and chemical stability, can enhance the mechanical strength and flexibility of the sealing grease, and improve its sealing effect in complex environments.

[0014] Preferably, the mass ratio of the bentonite, graphene, modified viscose fiber and chitosan is 1g:80-90mg:0.4-0.6g:0.1-0.2g.

[0015] By adopting the above technical solution, the mass ratio of bentonite, graphene, modified viscose fiber and chitosan is further limited within a certain range, and the modified bentonite obtained has better comprehensive performance. The high strength of graphene and the biopolymer characteristics of chitosan can enhance the mechanical strength and flexibility of the sealing grease and improve its sealing effect in complex environments. The water absorption and swelling properties of bentonite can further enhance the sealing and self-healing ability of the sealing grease. The addition of viscose fiber increases the ductility and tear resistance of the sealing grease, making it perform better in dynamic sealing environments.

[0016] The modified viscose fiber can be loaded on the surface of graphene, and the graphene loaded on the modified viscose fiber can be loaded on the surface of bentonite. Chitosan makes the bentonite, graphene and modified viscose fiber bond tightly, so that the modified bentonite has good thermal stability, chemical stability, mechanical properties and sealing properties. It is subsequently applied to an insulating sealing grease composition to obtain a sealing grease with good mechanical strength, flexibility, sealing and self-healing ability.

[0017] Preferably, the preparation method of the modified viscose fiber comprises the following steps: dispersing the viscose fiber in a sodium hydroxide solution, soaking for 1-2 hours, washing with water, shearing to a length of 1-2 mm, grinding, and then dispersing in deionized water, adding silver nanowires and hydroxyethyl cellulose, stirring for 2-3 hours, and drying to obtain the modified viscose fiber.

[0018] By adopting the above technical scheme, the viscose fiber is treated with sodium hydroxide solution, the surface properties of the viscose fiber are changed, the solubility of the viscose fiber is increased, the residual chemical substances are removed, and the purity and performance of the fiber are improved.

[0019] Silver nanowires can be loaded on the surface of viscose fibers, improving the antibacterial properties, compatibility and mechanical properties of viscose fibers. Hydroxyethyl cellulose has good film-forming and adhesive properties. Hydroxyethyl cellulose enhances the bonding force between silver nanowires and viscose fibers, improving the mechanical strength and stability of the modified adhesive fibers. It is subsequently applied to modified bentonite, increasing the bonding force between the components in the bentonite, making the modified bentonite have better comprehensive properties, and is subsequently applied to sealing grease, increasing the mechanical strength, sealing and stability of the sealing grease.

[0020] Preferably, the method for preparing the modified asbestos fiber comprises the following steps: (1) Cutting the asbestos fibers into small pieces of 3-5 mm in length, immersing them in an aqueous solution of ammonium chloride with a mass concentration of 5-20%, treating them at a temperature of 80-100° C. for 2-3 hours, and then dispersing them in anhydrous ethanol for washing, filtering, and drying to obtain pretreated asbestos fibers; (2) Dispersing the pretreated silica in deionized water, adding polyvinyl alcohol, and ultrasonicating for 1-2 hours to obtain a mixed solution for later use; (3) Dispersing the pretreated asbestos fibers of step (1) in deionized water, adding the mixed solution of step (2) and xanthan gum, stirring for 2-3 hours, and drying to obtain modified asbestos fibers.

[0021] By adopting the above technical scheme, asbestos fibers are treated with an aqueous solution of ammonium chloride, and the surface properties of the asbestos fibers are changed through chemical reactions. The ammonium ions in the ammonium chloride can react with the active groups on the surface of the asbestos fibers, affecting the charge state of the fibers, thereby changing their dispersibility in water and compatibility with other materials.

[0022] The pretreated silica is dispersed in deionized water, and the hydroxyl groups in the polyvinyl alcohol molecules can form hydrogen bonds with the hydroxyl groups on the surface of the silica. This hydrogen bonding effect helps to disperse the silica particles in the polyvinyl alcohol matrix to obtain a stable mixed solution.

[0023] Pretreated asbestos fibers are dispersed in deionized water, and mixed liquid and epoxy resin are added. White carbon black can be loaded on the surface of asbestos fibers, improving the dispersibility of asbestos fibers in deionized water and reducing agglomeration. Asbestos fibers have excellent heat resistance, chemical corrosion resistance and insulation properties, while white carbon black has a high specific surface area, good dispersibility and reinforcement effect. The combination of the two can enhance the mechanical properties, thermal stability and chemical stability of the composite material. Xanthan gum has a certain viscosity, which makes white carbon black and asbestos fibers adhere tightly, increasing the performance stability of modified asbestos fibers, and is subsequently applied to sealing grease compositions to improve the mechanical properties, thermal / chemical stability and sealing performance of the sealing grease compositions.

[0024] Preferably, the mass ratio of the asbestos fiber, pretreated white carbon black and xanthan gum is 1:0.4-0.5:0.1-0.2.

[0025] By adopting the above technical scheme, the mass ratio of asbestos fiber, pretreated silica and xanthan gum is further limited within a certain range, and the comprehensive performance of asbestos fiber is improved. Asbestos fiber has good heat resistance and chemical stability, and pretreated silica can improve the viscosity and consistency of sealing grease. The combination of the two can form a tighter sealing layer and improve the sealing effect. Xanthan gum makes the pretreated silica and asbestos fiber bond tightly, and there is a synergistic effect between asbestos fiber, pretreated silica and xanthan gum, so that the modified asbestos fiber has better chemical stability, heat resistance, mechanical properties and sealing performance.

[0026] Preferably, the method for preparing the pretreated white carbon black comprises the following steps: dispersing the white carbon black in a silane coupling agent aqueous solution, stirring at a temperature of 70-80° C. for 1-2 hours, adding sodium dodecyl sulfate and nano titanium dioxide, continuing to stir, filtering, and drying to obtain the pretreated white carbon black.

[0027] By adopting the above technical solution, the silane coupling agent can reduce the interaction force between silica particles and reduce secondary agglomeration by reacting with the hydroxyl groups on the surface of silica, thereby significantly improving the dispersibility of silica in water.

[0028] White carbon black can improve the consistency and viscosity of sealing grease, form a tighter sealing layer, and enhance the sealing effect. Nano-titanium dioxide has good chemical stability and can improve the resistance of sealing grease to acids, alkalis, solvents and other chemical substances, extending the service life of sealing grease. Nano-titanium dioxide can be loaded in the pores and surface of white carbon black, further improving the weather resistance and corrosion resistance of sealing grease, and enhancing its sealing performance in harsh environments.

[0029] Sodium dodecyl sulfate improves the dispersibility of white carbon black and nano titanium dioxide in the sealing grease matrix, prevents particle agglomeration, and improves the stability of the sealing grease, avoiding stratification or precipitation during storage and use. White carbon black, sodium dodecyl sulfate and nano titanium dioxide are combined to improve the mechanical properties, chemical stability, heat resistance and sealing performance of the system. The obtained pretreated white carbon black has better comprehensive properties and is subsequently used in the sealing grease composition to improve the comprehensive performance of the composition.

[0030] Preferably, the base oil is selected from one or more of saturated polyol esters, diesters, complex esters, aromatic esters and vegetable oils.

[0031] By adopting the above technical solution, ester oil can greatly improve the anti-wear performance of base oil, and can achieve good anti-wear effect even at low concentrations (such as 5-10%). It also has good chemical stability and can resist the erosion of chemical substances such as acids, alkalis, and solvents, thereby extending the service life of lubricating materials, especially in harsh chemical environments.

[0032] Preferably, the antioxidant is selected from amine antioxidants or phenolic antioxidants.

[0033] By adopting the above technical solution, amine and phenol antioxidants can effectively inhibit the aging process of polymers in a hot oxygen environment, and prevent the breakage and cross-linking of polymer molecular chains by interrupting free radical chain reactions, thereby maintaining the mechanical properties and appearance of the material. Antioxidants can also resist the erosion of chemical substances such as acids, alkalis, and solvents, thereby extending the service life of polymer materials.

[0034] In the second aspect, the present application also provides a method for preparing an insulating sealing grease composition, comprising the following steps: heating the base oil to 90-95°C, adding a rust inhibitor and a thickener, raising the temperature to 120-125°C, keeping warm for 60-65 minutes, adding modified bentonite, calcium carbonate, modified asbestos fiber, a surface modifier, and an antioxidant, and performing a constant temperature and pressure dehydration reaction at a vacuum degree of -0.05--0.1MPa to obtain a mixture, rolling and grinding the mixture to obtain an insulating sealing grease composition.

[0035] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing the insulating sealing grease composition. The obtained insulating sealing grease composition has good mechanical properties, wear resistance and sealing properties.

[0036] In summary, this application has the following beneficial effects: 1. The insulating sealing grease composition obtained by mixing the various components in the present application has excellent electrical insulation performance, sealing, and temperature resistance, can provide mechanical protection and sealing for components, reduce damage caused by vibration, impact and wear, and extend the service life of components.

[0037] 2. The modified bentonite in the present application has good colloidal properties, can effectively thicken the base oil, form a stable colloidal structure, and make the sealing grease difficult to flow. The modified bentonite can swell when in contact with water, fill irregular voids, enhance the sealing performance of the sealing grease, and improve the temperature resistance and chemical stability of the composition.

[0038] 3. The modified asbestos fiber in this application has high tensile strength, can significantly enhance the mechanical strength of the sealing grease, improve its wear resistance and pressure resistance, and also has good high temperature resistance, sealing and chemical stability, which can enhance the stability and reliability of the sealing grease in high temperature environment and ensure that it maintains its physical and chemical properties in a wider temperature range. DETAILED DESCRIPTION

[0039] The present application is further described in detail below with reference to the embodiments.

[0040] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0041] Preparation example of modified bentonite Preparation Example 1-1 The preparation method of modified bentonite comprises the following steps: (1) Disperse 1.2 kg of bentonite and 0.3 kg of dimethyl octadecyl quaternary ammonium salt in 2 L of deionized water, stir at 65 °C for 35 min, filter, and dry to obtain pretreated bentonite; the dimethyl octadecyl quaternary ammonium salt is quaternary ammonium salt-18, purchased from Hubei Shineng Chemical Technology Co., Ltd.; (2) dispersing graphene in 1.2 L of deionized water, adding 0.05 g of Triton X-100 and modified viscose fiber, stirring at 5500 rpm for 25 min, and drying to obtain pretreated graphene; (3) The pretreated bentonite prepared in step (1) was dispersed in 3.5 L of 10% acetic acid solution, and the pretreated graphene and chitosan prepared in step (2) were added. The mixture was stirred at 75° C. for 3 h and dried to obtain modified bentonite.

[0042] The mass ratio of bentonite, graphene, modified viscose fiber and chitosan is 1g:90mg:0.4g:0.1g.

[0043] The preparation method of modified viscose fiber comprises the following steps: dispersing 1 kg of viscose fiber in 2 L of sodium hydroxide solution with a mass fraction of 12%, soaking for 1.5 hours, washing with water, cutting to a length of 1-2 mm, grinding, and then dispersing in 3 L of deionized water, adding 0.3 kg of silver nanowires and 0.1 kg of hydroxyethyl cellulose, stirring for 3 hours, and drying to obtain modified viscose fiber.

[0044] Viscose fiber was purchased from Shandong Fuhui Textile Technology Co., Ltd.

[0045] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no graphene is added.

[0046] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (2), no modified viscose fiber is added.

[0047] Preparation Example 1-4 The difference from Preparation Example 1-1 is that in step (3), chitosan is not added.

[0048] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of bentonite, graphene, modified viscose fiber and chitosan is 1g:80mg:0.6g:0.2g.

[0049] Preparation Example 1-6 The difference from Preparation Example 1-1 is that the mass ratio of bentonite, graphene, modified viscose fiber and chitosan is 1g:60mg:0.1g:0.8g.

[0050] Preparation Example 1-7 The difference from Preparation Example 1-1 is that no silver nanowires are added in the preparation method of the modified viscose fiber.

[0051] Preparation Example 1-8 The difference from Preparation Example 1-1 is that hydroxyethyl cellulose is not added in the preparation method of the modified viscose fiber.

[0052] Preparation example of modified asbestos fiber Preparation Example 2-1 The preparation method of modified asbestos fiber comprises the following steps: (1) 1.5 kg of asbestos fibers were cut into small pieces of 3-5 mm in length, immersed in 3 L of 5% ammonium chloride aqueous solution, treated at 90°C for 3 h, then dispersed in 5 L of anhydrous ethanol for washing, filtering, and drying to obtain pretreated asbestos fibers; (2) Disperse the pretreated silica in 2 L of deionized water, add 0.1 kg of polyvinyl alcohol, and ultrasonicate for 2 h to obtain a mixed solution for later use; (3) The pretreated asbestos fibers of step (1) were dispersed in 2 L of deionized water, and the mixed solution of step (2) and xanthan gum were added, stirred for 3 h, and dried to obtain modified asbestos fibers.

[0053] The mass ratio of asbestos fiber, pretreated silica and xanthan gum is 1:0.4:0.1.

[0054] The preparation method of pretreated white carbon black comprises the following steps: dispersing 2 kg of white carbon black in 3 L of 0.02% by mass silane coupling agent KH550 aqueous solution, stirring at a temperature of 76° C. for 2 hours, adding 0.06 kg of sodium dodecyl sulfate and 0.3 kg of nano titanium dioxide, continuing stirring, filtering, and drying to obtain pretreated white carbon black.

[0055] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no pretreated silica is added.

[0056] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), no xanthan gum is added.

[0057] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of asbestos fiber, pretreated silica and xanthan gum is 1:0.5:0.2.

[0058] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of asbestos fiber, pretreated silica and xanthan gum is 1:0.1:0.5.

[0059] Preparation Example 2-6 The difference from Preparation Example 2-1 is that sodium dodecyl sulfate is not added in the preparation method of pretreated silica.

[0060] Preparation Example 2-7 The difference from Preparation Example 2-1 is that in the preparation method of pretreated white carbon black, no nano titanium dioxide is added.

[0061] Example

[0062] Example 1 An insulating sealing grease composition comprises the following raw materials by weight: 90 kg of base oil, 2.5 kg of rust inhibitor, 7 kg of thickener, 11 kg of modified bentonite, 4 kg of calcium carbonate, 12 kg of modified asbestos fiber, 1.6 kg of surface modifier, and 2.4 kg of antioxidant; The base oil is selected from saturated polyol ester, specifically saturated polyol ester Priolube 3970, purchased from Dongguan Hersby New Materials Co., Ltd. The rust inhibitor is 2,5-disulfide-1,3,4-thiadiazole derivative T561, the thickener is polytrifluorochloroethylene powder, item number M300H, purchased from Dongguan Hongming New Materials Co., Ltd.; the surface modifier is dimethyldiethoxysilane, and the antioxidant is selected from antioxidant 5057.

[0063] The preparation method of the above-mentioned insulating sealing grease composition includes the following steps: heating the base oil to 95°C, adding a rust inhibitor and a thickener, raising the temperature to 125°C, keeping the temperature for 65 minutes, then adding modified bentonite, calcium carbonate, modified asbestos fiber, a surface modifier, and an antioxidant, and performing a constant temperature and pressure dehydration reaction under a vacuum degree of -0.05MPa to obtain a mixture, rolling and grinding the mixture to obtain the insulating sealing grease composition.

[0064] The modified bentonite was prepared by using Preparation Example 1-1; and the modified asbestos fiber was prepared by using Preparation Example 2-1.

[0065] Example 2 An insulating sealing grease composition, which differs from Example 1 in that it comprises the following raw materials, by weight: 60 kg of base oil, 3.5 kg of rust inhibitor, 12 kg of thickener, 15 kg of modified bentonite, 6 kg of calcium carbonate, 8 kg of modified asbestos fiber, 1.8 kg of surface modifier, and 2.7 kg of antioxidant.

[0066] Example 3 An insulating sealing grease composition is different from Example 1 in that the modified bentonite is prepared using Preparation Example 1-2.

[0067] Example 4 An insulating sealing grease composition is different from Example 1 in that the modified bentonite is prepared using Preparation Examples 1-3.

[0068] Example 5 An insulating sealing grease composition is different from Example 1 in that the modified bentonite is prepared using Preparation Examples 1-4.

[0069] Example 6 An insulating sealing grease composition is different from Example 1 in that the modified bentonite is prepared using Preparation Examples 1-5.

[0070] Example 7 An insulating sealing grease composition is different from Example 1 in that the modified bentonite is prepared using Preparation Examples 1-6.

[0071] Example 8 An insulating sealing grease composition is different from Example 1 in that the modified bentonite is prepared using Preparation Examples 1-7.

[0072] Example 9 An insulating sealing grease composition is different from Example 1 in that the modified bentonite is prepared using Preparation Examples 1-8.

[0073] Example 10 An insulating sealing grease composition, which is different from Example 1 in that the modified asbestos fiber is prepared using Preparation Example 2-2.

[0074] Embodiment 11 An insulating sealing grease composition is different from Example 1 in that the modified asbestos fiber is prepared using Preparation Example 2-3.

[0075] Example 12 An insulating sealing grease composition is different from Example 1 in that the modified asbestos fiber is prepared using Preparation Examples 2-4.

[0076] Example 13 An insulating sealing grease composition is different from Example 1 in that the modified asbestos fiber is prepared using Preparation Examples 2-5.

[0077] Embodiment 14 An insulating sealing grease composition is different from Example 1 in that the modified asbestos fiber is prepared using Preparation Examples 2-6.

[0078] Embodiment 15 An insulating sealing grease composition is different from Example 1 in that the modified asbestos fiber is prepared using Preparation Examples 2-7.

[0079] Comparative Example Comparative Example 1 An insulating sealing grease composition, which differs from Example 1 in that modified bentonite is not added.

[0080] Comparative Example 2 An insulating sealing grease composition, which differs from Example 1 in that the modified bentonite is replaced by an equal amount of bentonite.

[0081] Comparative Example 3 An insulating sealing grease composition, which differs from Example 1 in that no modified asbestos fiber is added.

[0082] Comparative Example 4 An insulating sealing grease composition, which differs from Example 1 in that the modified asbestos fiber is replaced by an equal amount of asbestos fiber.

[0083] Performance testing The insulating sealing grease compositions prepared in Examples 1-15 and Comparative Examples 1-4 were subjected to performance tests. The reference standards for various performance tests are listed in Table 1. The test results are shown in Table 1.

[0084] Table 1 Test data of embodiments and comparative examples

[0085] It can be seen from Table 1 that the insulating sealing grease compositions prepared in Examples 1-2 of the present application have good sealing, stability, wear resistance and durability. Among them, the cone penetration of Example 1 is 60 mm, the evaporation loss is 0.08 w / w%, the oil separation is 0, and the air permeability is 2 cm 3 , the friction coefficient is 0.47, and the change rate of cone penetration in the aging test is 1.5%. This shows that the prepared insulating sealing grease composition has excellent electrical insulation performance, sealing performance, and temperature resistance, and improves the chemical stability of the sealing grease composition, so that it can still maintain good performance in harsh environments.

[0086] In the preparation method of modified bentonite in Examples 3-5, graphene, modified viscose fiber and chitosan are not added respectively. In Examples 6-7, the mass ratio of bentonite, graphene, modified viscose fiber and chitosan is changed. It can be seen from Table 1 that the cone penetration, evaporation loss, oil separation, air permeability, friction coefficient and cone penetration change rate of aging test in Examples 3-5 are worse than those in Examples 1-2 and 6. The above performance effects of Example 7 are better than those in Examples 3-5, but worse than those in Examples 1-2 and 6, indicating that the high strength of graphene and the biopolymer characteristics of chitosan can enhance the mechanical strength and flexibility of the sealing grease and improve its sealing effect in complex environments. The water absorption and swelling properties of bentonite can further enhance the sealing and self-healing ability of the sealing grease. The addition of viscose fiber increases the ductility and tear resistance of the sealing grease, making it perform better in a dynamic sealing environment.

[0087] In the preparation method of the modified viscose fiber of Examples 8-9, silver nanowires and hydroxyethyl cellulose are not added respectively. As can be seen from Table 1, the cone penetration, evaporation loss, oil separation, air permeability, friction coefficient, and cone penetration change rate of Examples 8-9 are better than those of Example 4, but worse than those of Examples 1-2, indicating that silver nanowires can be loaded on the surface of viscose fibers, thereby improving the antibacterial properties, compatibility and mechanical properties of viscose fibers. Hydroxyethyl cellulose has good film-forming properties and adhesion. Hydroxyethyl cellulose enhances the bonding force between silver nanowires and viscose fibers, and is subsequently applied to modified bentonite to increase the bonding force between the components in the bentonite, thereby subsequently increasing the mechanical strength, sealing property and stability of the sealing grease.

[0088] In the preparation method of the modified asbestos fiber of Examples 10-11, no pre-treated white carbon black and xanthan gum are added respectively. The mass ratio of asbestos fiber, white carbon black and xanthan gum is changed in Examples 12-13. As can be seen from Table 1, the cone penetration, evaporation loss, oil separation, air permeability, friction coefficient and aging test cone penetration change rate of Examples 10-11 are all worse than those of Examples 1-2 and Example 12. The above performance effects of Example 13 are better than those of Examples 10-11, but worse than those of Examples 1-2 and Example 12, indicating that the asbestos fiber has good heat resistance and chemical stability. White carbon black can increase the viscosity and consistency of the sealing grease. The combination of the two can form a tighter sealing layer and improve the sealing effect. Xanthan gum makes the white carbon black and asbestos fiber bond tightly. The modified asbestos fiber has better chemical stability, heat resistance, mechanical properties and sealing performance.

[0089] In the preparation method of the pretreated silica in Examples 14-15, sodium dodecyl sulfate and nano-titanium dioxide are not added respectively. As can be seen from Table 1, the cone penetration, evaporation loss, oil separation, air permeability, friction coefficient, and cone penetration change rate of Examples 14-15 are better than those of Example 10, but worse than those of Examples 1-2, indicating that the combination of silica, sodium dodecyl sulfate and nano-titanium dioxide improves the mechanical properties, chemical stability, heat resistance and sealing properties of the system, and the obtained pretreated silica has better comprehensive properties, which is subsequently used in the sealing grease composition to improve the comprehensive properties of the composition.

[0090] Comparative Examples 1 and 3 do not add modified bentonite and modified asbestos fiber, respectively. As can be seen from Table 1, compared with Example 1, the performance test results of cone penetration, evaporation loss, oil separation, air permeability, friction coefficient, and aging test cone penetration change rate of Comparative Examples 1 and 3 are significantly worse than those of Examples 1-2, indicating that the modified bentonite has good colloidal properties, can effectively thicken the base oil, fill irregular voids, enhance the sealing performance of the sealing grease, and improve the temperature resistance and chemical stability of the composition; the modified asbestos fiber has a high tensile strength, can significantly enhance the mechanical strength of the sealing grease, improve its wear resistance and pressure resistance, and make it not easily damaged when subjected to mechanical stress.

[0091] In Comparative Examples 2 and 4, the modified bentonite is replaced by an equal amount of bentonite, and the modified asbestos fiber is replaced by an equal amount of asbestos fiber. It can be seen from Table 1 that compared with Example 1, the test results of the cone penetration, evaporation loss, oil separation, air permeability, friction coefficient, and aging test cone penetration change rate of Comparative Examples 2 and 4 are significantly worse than those of Examples 1-2, but better than those of Comparative Examples 1 and 3, indicating that the modified bentonite and modified asbestos fiber of the present application have good mechanical properties, mechanical properties and air tightness, and maintain the structural strength and performance stability of the sealing grease composition.

[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. An insulating sealing grease composition, characterized in that: The raw materials are as follows, calculated by weight: 60-90 parts of base oil, 2.5-3.5 parts of rust inhibitor, 7-12 parts of thickener, 11-15 parts of modified bentonite, 4-6 parts of calcium carbonate, 8-12 parts of modified asbestos fiber, 1.6-1.8 parts of surface modifier and 2.4-2.7 parts of antioxidant.

2. An insulating sealing grease composition according to claim 1, characterized in that: The preparation method of the modified bentonite comprises the following steps: (1) dispersing bentonite and dimethyl octadecyl quaternary ammonium salt in deionized water, stirring at a temperature of 60-65° C. for 30-35 minutes, filtering, and drying to obtain pretreated bentonite; (2) dispersing graphene in deionized water, adding Triton X-100 and modified viscose fiber, stirring at a speed of 5000-5500 rpm for 20-25 min, and drying to obtain pretreated graphene; (3) Dispersing the pretreated bentonite in step (1) in an acetic acid solution, adding the pretreated graphene and chitosan in step (2), stirring at a temperature of 70-75° C. for 2-3 h, and drying to obtain modified bentonite.

3. An insulating sealing grease composition according to claim 2, characterized in that: The mass ratio of the bentonite, graphene, modified viscose fiber and chitosan is 1g:80-90mg:0.4-0.6g:0.1-0.2g.

4. An insulating sealing grease composition according to claim 2, characterized in that: The preparation method of the modified viscose fiber comprises the following steps: dispersing the viscose fiber in a sodium hydroxide solution, soaking for 1-2 hours, washing with water, cutting to a length of 1-2 mm, grinding, and then dispersing in deionized water, adding silver nanowires and hydroxyethyl cellulose, stirring for 2-3 hours, and drying to obtain the modified viscose fiber.

5. The insulating sealing grease composition according to claim 1, characterized in that: The preparation method of the modified asbestos fiber comprises the following steps: (1) Cutting the asbestos fibers into small pieces of 3-5 mm in length, immersing them in an aqueous solution of ammonium chloride with a mass concentration of 5-20%, treating them at a temperature of 80-100° C. for 2-3 hours, and then dispersing them in anhydrous ethanol for washing, filtering, and drying to obtain pretreated asbestos fibers; (2) Dispersing the pretreated silica in deionized water, adding polyvinyl alcohol, and ultrasonicating for 1-2 hours to obtain a mixed solution for later use; (3) Dispersing the pretreated asbestos fibers of step (1) in deionized water, adding the mixed solution of step (2) and xanthan gum, stirring for 2-3 hours, and drying to obtain modified asbestos fibers.

6. An insulating sealing grease composition according to claim 5, characterized in that: The mass ratio of the asbestos fiber, pretreated white carbon black and xanthan gum is 1:0.4-0.5:0.1-0.

2.

7. An insulating sealing grease composition according to claim 5, characterized in that: The preparation method of the pretreated white carbon black comprises the following steps: dispersing the white carbon black in a silane coupling agent aqueous solution, stirring for 1-2 hours at a temperature of 70-80° C., adding sodium dodecyl sulfonate and nano titanium dioxide, continuing stirring, filtering, and drying to obtain the pretreated white carbon black.

8. The insulating sealing grease composition according to claim 1, characterized in that: The base oil is selected from one or more of saturated polyol esters, diesters, complex esters, aromatic esters and vegetable oils.

9. The insulating sealing grease composition according to claim 1, characterized in that: The antioxidant is selected from amine antioxidants or phenolic antioxidants.

10. The method for preparing an insulating sealing grease composition according to claim 1, characterized in that: The method comprises the following steps: heating the base oil to 90-95°C, adding a rust preventer and a thickener, raising the temperature to 120-125°C, keeping the temperature for 60-65 minutes, adding modified bentonite, calcium carbonate, modified asbestos fiber, a surface modifier and an antioxidant, and performing a constant temperature and pressure dehydration reaction at a vacuum degree of -0.05-0.1MPa to obtain a mixture, and rolling and grinding the mixture to obtain an insulating sealing grease composition.

Citation Information

Patent Citations

  • High-strength waterproof flame-retardant seal coating and preparation method thereof

    CN104592846A

  • Single component silane modified sealant used in industrialized building

    CN108165230A

  • Organic bentonite lubricating grease and preparation method thereof

    CN115851345A

  • Wire insulating shell and preparation method thereof

    CN117777589A

  • Environment-friendly high-pressure sealing grease composition and preparation method thereof

    CN118185685A